2006
DOI: 10.1007/s00028-006-0214-6
|View full text |Cite
|
Sign up to set email alerts
|

Carleman estimates for one-dimensional degenerate heat equations

Abstract: In this paper, we are interested in controllability properties of parabolic equations degenerating at the boundary of the space domain.We derive new Carleman estimates for the degenerate parabolic equationwhere the function a mainly satisfies 1)), a > 0 on (0, 1) and 1 √ a ∈ L 1 (0, 1).We are mainly interested in the situation of a degenerate equation at the boundary i.e. in the case where a(0) = 0 and/or a(1) = 0. A typical example is a(x) = x α (1 − x) β with α, β ∈ [0, 2). As a consequence, we deduce null c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 30 publications
0
104
0
Order By: Relevance
“…Then, null controllability holds if and only if γ ∈ (0, 1) (see [13,14]), while, for γ ≥ 1, the best result one can show is regional null controllability(see [12]), which consists in controlling the solution within the domain of inuence of the control. Several extensions of the above results are available in one space dimension, see [1,34] for equations in divergence form, [11,10] for nondivergence form operators, and [9,24] for cascade systems.…”
Section: Boundary-degenerate Parabolic Equationsmentioning
confidence: 92%
“…Then, null controllability holds if and only if γ ∈ (0, 1) (see [13,14]), while, for γ ≥ 1, the best result one can show is regional null controllability(see [12]), which consists in controlling the solution within the domain of inuence of the control. Several extensions of the above results are available in one space dimension, see [1,34] for equations in divergence form, [11,10] for nondivergence form operators, and [9,24] for cascade systems.…”
Section: Boundary-degenerate Parabolic Equationsmentioning
confidence: 92%
“…Several extensions of the above results are available in one space dimension, see [1,37] for equations in divergence form, [11,10] for nondivergence form operators, and [9,25] for cascade systems. Fewer results are available for multidimensional problems, mainly in the case of two dimensional parabolic operators which simply degenerate in the normal direction to the boundary of the space domain, see [15].…”
Section: Xxxiv-5mentioning
confidence: 88%
“…In the case of γ ∈ [1/2, 1], our weight β will be the classical one. On the other hand, for γ ∈ (0, 1/2) we follow the strategy of [1,11,37], adapting the weight β to the nonsmooth coefficient |x| 2γ .…”
Section: A Global Carleman Estimatementioning
confidence: 99%
“…In this paper, we investigate the approximate controllability of the coupled degenerate system Recently, the controllability of the following degenerate parabolic equation has been investigated; see references [1][2][3][4][5]: u t -x p u x x + c(x, t)u = hχ ω , (x, t) ∈ (0, 1) × (0, T), (1.6) where c ∈ L ∞ ((0, 1) × (0, T)). The degenerate equation (1.6) can be obtained by suitable transformations of the Prandtl equations; see [6].…”
Section: Introductionmentioning
confidence: 99%
“…The authors prove that the problem (1.6), (1.7) or (1.8) and (1.9) is null controllable if 0 < p < 2, and the problem is not null controllable if p ≥ 2, see the references [1][2][3][4][5]. On the other hand, it is shown that, for every p > 0, the problem (1.6), (1.7) or (1.8) and (1.9) is approximate controllability; see [7,8].…”
Section: Introductionmentioning
confidence: 99%